2022
DOI: 10.3389/fcell.2022.837574
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cholesterol Transport in Dendritic Cells Defines Optimal Exogenous Antigen Presentation and Toxoplasma gondii Proliferation

Abstract: Dendritic cells are the most powerful antigen-presenting cells of the immune system. They present exogenous antigens associated with Major Histocompatibility Complex (MHC) Class II molecules through the classical pathway to stimulate CD4+ T cells, or with MHC-I to activate CD8+ T lymphocytes through the cross-presentation pathway. DCs represent one of the main cellular targets during infection by Toxoplasma gondii. This intracellular parasite incorporates essential nutrients, such as cholesterol, to grow and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…HIV and vaccinia virus budding from host cells requires ESCRT-III components ( 64 , 65 ), while exosomal secretion of infectious prions is regulated by ESCRT-dependent and ESCRT-independent pathways ( 66 ). The apicomplexan parasite, Toxoplasma gondii , lives in a parasitophorous vacuole that acquires ESCRT machinery for transport of cholesterol and host proteins across its membrane ( 67 70 ). Ehrlichia chaffeensis , which is in the family Anaplasmataceae with A. phagocytophilum , similarly requires cholesterol and occupies a vacuole that receives cholesterol and host cell membranes, is full of ILVs, and is positioned adjacent to, but does not fuse with, MVBs ( 21 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…HIV and vaccinia virus budding from host cells requires ESCRT-III components ( 64 , 65 ), while exosomal secretion of infectious prions is regulated by ESCRT-dependent and ESCRT-independent pathways ( 66 ). The apicomplexan parasite, Toxoplasma gondii , lives in a parasitophorous vacuole that acquires ESCRT machinery for transport of cholesterol and host proteins across its membrane ( 67 70 ). Ehrlichia chaffeensis , which is in the family Anaplasmataceae with A. phagocytophilum , similarly requires cholesterol and occupies a vacuole that receives cholesterol and host cell membranes, is full of ILVs, and is positioned adjacent to, but does not fuse with, MVBs ( 21 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MCD in DC–T cell interaction are also observed by other groups 79–81 . Importantly, the reduction of cell surface cholesterol in DCs impairs their function against promoting the clearance of Toxoplasma gondii and hepatitis B virus in vivo, 82,83 highlighting that cholesterol in the plasma membrane serves important roles in facilitating T‐cell priming and adaptive immune responses. Further, APOE (encoded by Apoe ) is an important cholesterol and lipid carrier, Apoe ‐deficient primary splenic DCs accumulate more intracellular cholesterol.…”
Section: Cholesterol and Its Metabolitesmentioning
confidence: 57%
“…75,76 The effects of MCD in DC-T cell interaction are also observed by other groups. [79][80][81] Importantly, the reduction of cell surface cholesterol in DCs impairs their function against promoting the clearance of Toxoplasma gondii and hepatitis B virus in vivo, 82,83 highlighting that cholesterol in the plasma membrane serves important roles in Beyond regulation of signal 1, additional studies have shown that cholesterol levels can influence DC migration and cytokine production. Indeed, increasing cholesterol levels using a high-cholesterol diet or ablation of Apoe in mice dampens the migration of DCs to the lymph node, lowering cholesterol levels can partially reverse these migration defects.…”
Section: Cholesterolmentioning
confidence: 99%
“…A recent report showed that dendritic cells infected with T . gondii up-regulate the expression of the ESCRT-III component CHMP4B and that CHMP4B is associated with the PV [ 159 ]. The same study showed that blocking cholesterol trafficking impaired MHC-I and MHC-II presentation of parasite antigens, reduced PV recruitment of CHMP4B, and suppressed parasite replication [ 159 ].…”
Section: Overview Of the Host Endosomal Sorting Complex Required For ...mentioning
confidence: 99%
“…gondii up-regulate the expression of the ESCRT-III component CHMP4B and that CHMP4B is associated with the PV [ 159 ]. The same study showed that blocking cholesterol trafficking impaired MHC-I and MHC-II presentation of parasite antigens, reduced PV recruitment of CHMP4B, and suppressed parasite replication [ 159 ]. Although the role of the ESCRT machinery in linking these phenotypes hasn’t been elucidated, it would be interesting to know if up-regulation of ESCRT components negatively regulates antigen presentation.…”
Section: Overview Of the Host Endosomal Sorting Complex Required For ...mentioning
confidence: 99%